On the metals compatibility assessment for oxygen service. (January 2022) - Shunmugasamy, Vasanth C.; Chiffoleau, Gwenael J.A.; Forsyth, Elliot; Laycock, Nicholas J.; Kruijer, Alfred; Mansoor, Bilal
Abstract: This review article critically analyzes the selection and compatibility assessment framework of metallic alloys in pure oxygen (>99.5%) atmospheres using promoted combustion and particle impact ignition tests in combination with the Pressure-Velocity (PV) curves. The historical test data for four important metallic alloys frequently used in the oil and gas industry, namely nickel alloys C276 and 600, stainless steel 304 and 316, are mined and analyzed to: (i) capture trends and correlation of data obtained by these two tests with the PV curves, (ii) identify gaps in the data for critical process variables such as temperature, pressure and gas velocity, (iii) identify limitations of the two tests, (iv) understand the relevance of shape factors and geometry of test samples and flowing vs. non-flowing conditions on test results and (v) evaluate whether exemption pressures and PV curves can be extended or adjusted for important metals to accommodate more demanding conditions. In industry practices, PV curves are utilized to impose velocity limitations in oxygen systems to help mitigate particle impact ignition when the operating pressures are greater than alloys exemption pressures. Our analysis shows, current version of PV curves - based primarily on historical data and industry experience are conservative, limited to specific thicknesses and available only up to 200 °C for both exempt and non-exempt alloys. For the oil and gas industry where conditions up to 300°C and 80 bar are desired, there is a need to conduct new testing to develop guidelines for thinner cross-sections and more demanding operating conditions including higher temperatures and pressures.This will open avenues for new innovations and applications of gaseous oxygen and help industries operate their plants with higher efficiencies. Highlights: Critical analysis of selection and compatibility assessment framework of metallic alloys in enriched oxygen (> 99.5%). Metals selection for enriched oxygen applications based on promoted combustion testing and particle impact assessment. Promoted combustion test results are influenced by oxygen temperature, pressure, flowing condition and specimen geometry effects. Particle impact assessment, cannot directly compare with literature, unless test system conforms or exceeds system severity. Though PV curves impose velocity limits - evaluate materials for particle impact under similar impingement configuration.